Predicting the Trajectory of Participation After Traumatic Brain Injury: A Longitudinal Analysis. Issue 4 (July 2018) - Erler, Kimberly S.; Whiteneck, Gale G.; Juengst, Shannon B.; Locascio, Joseph J.; Bogner, Jennifer A.; Kaminski, Jamie; Giacino, Joseph T.
Abstract : Objective: To identify factors that predict trajectories of participation over the first 5 years after moderate to severe traumatic brain injury (TBI). Setting: TBI Model System Programs. Participants: Community-dwelling individuals with TBI, 16 years of age or older ( n = 1947). Design: Secondary analysis of a prospective, nonrandomly sampled, longitudinal data registry. Main Measures: Participation Assessment with Recombined Tools—Objective (PART-O). Results: Age at injury and FIM Motor score predicted trajectory of participation over the first 5 years after moderate to severe TBI. Older age predicted generally worse participation overall as well as progressively worsening participation over time. Higher FIM Motor raised the predicted participation values, although it reduced the rate of improvement in participation scores over time. FIM Cognitive scores, race, depression, years of education, and living setting did not predict trajectory but did significantly influence participation consistently at all time points. Conclusion: The trajectories of participation over the first 5 years after TBI can be predicted by age at injury and FIM Motor scores. These findings may enhance the ability of rehabilitation professionals to identify individuals at risk for poor participation after TBI and develop targeted interventions for optimizing involvement in life activities.